Fundamental parameters of the massive eclipsing binary HM1 8. Issue 2 (12th October 2021) - Rodríguez, C N; Ferrero, G A; Benvenuto, O G; Gamen, R; Morrell, N I; Barbá, R H; Arias, J; Massey, P
ABSTRACT: We present a comprehensive study of the massive binary system HM1 8, based on multi-epoch high-resolution spectroscopy, V -band photometry, and archival X-ray data. Spectra from the OWN Survey, a high-resolution optical monitoring of Southern O and WN stars, are used to analyse the spectral morphology and perform quantitative spectroscopic analysis of both stellar components. The primary and secondary components are classified as O4.5 IV(f) and O9.7 V, respectively. From a radial velocity (RV) study, we derived a set of orbital parameters for the system. We found an eccentric orbit ( e  = 0.14 ± 0.01) with a period of P  = 5.87820 ± 0.00008 d. Through the simultaneous analysis of the RVs and the V -band light curve, we derived an orbital inclination of 70.0° ± 2.0 and stellar masses of $M_a=33.6^{+1.4}_{-1.2}~\text{M}_{\odot }$ for the primary, and $M_b=17.7^{+0.5}_{-0.7}~\text{M}_{\odot }$ for the secondary. The components show projected rotational velocities v a sin  i  = 105 ± 14 km s −1 and v b sin  i  = 82 ± 15 km s −1, respectively. A tidal evolution analysis is also performed and found to be in agreement with the orbital characteristics. Finally, the available X-ray observations show no evidence of a colliding winds region; therefore, the X-ray emission is attributed to stellar winds.